Impact of Islamic Education in Addressing the Problems of Out-of-School Children in Northern Nigeria - Umar Alhaji Umar; Mohammed Alhaji Bukar (Walidem Institute and Publishing (WIP), 2025)
Objective: The objective of this study is to assess the role of Islamic education in addressing the issue of out-of-school children, focusing on how it can improve access to education, enhance learning outcomes, and create a supportive environment for children’s intellectual, spiritual, and moral growth. Theoretical framework: The study is based on theories of educational access, equity, and holistic education, focusing on how Islamic education can contribute to reducing educational exclusion and promoting well-rounded development. Literature review: The review explores the barriers faced by disadvantaged children in accessing education, such as financial constraints and inadequate facilities, while highlighting the potential of Islamic education to provide inclusive, moral, and intellectual growth. Method: A qualitative approach was used, involving case studies, interviews, and site visits to Islamic schools and community-based education initiatives to explore the challenges and benefits of Islamic education. Results: The results indicate that Islamic education plays a significant role in providing education to children who are otherwise excluded from the formal education system. While it offers a balanced approach that fosters intellectual, moral, and spiritual development, the study also identifies several challenges, including limited resources, inadequate facilities, and a shortage of trained teachers. Despite these obstacles, Islamic education has shown promise in improving learning outcomes and providing an enabling environment for children’s growth. Implications: The findings suggest that Islamic education should be considered in education policy to address the out-of-school children issue, with investments in resources, facilities, and teacher training to improve quality and access. Novelty: This study highlights the underexplored role of Islamic education in resolving the out-of-school children issue, providing a unique perspective on non-formal education as a solution to educational exclusion.